Modelling to Drive Design: Honing the SU+RE House through Performance Simulations. (3rd January 2018) - May, Ed
Abstract : Digital simulation technologies are for the first time allowing designers to directly study and impact the flows of energy, water, air, heat and sound which affect a building's occupants. The SU+RE House is a prime example of this. Guest‐EditorEd May, one of the Stevens Institute of Technology faculty leaders for the project and also a partner in the Brooklyn‐based design and consulting firm BLDGtyp, looks closely at how it demonstrated the possibilities of integrating data and environmental analysis techniques into the architectural design process, to produce truly sustainable and resilient buildings.